Analisis Rekonsiliasi Fiskal Laporan Keuangan Komersial Untuk Menentukan PPh Terutang PT. Mata Indah Nusantara - Dali, Rahmat Mulyana; Hanafi, Muhammad (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of the study is to determine the cause of the difference between the commercial financial statements that are done through the taxpayer on the fiscal financial statements in accordance with general provisions and taxation procedures. And to determine how the process of preparing the fiscal reconciliation is carried out at PT Mata Indah Nusantara in the 2020 fiscal year. The method determined through the research is a comparative descriptive method, which is a method that illustrates the commercial budget to be analyzed, and comparative, namely comparing the commercial budget prepared by the taxpayer, with the fiscal budget that has been calculated by the author.The results of the study indicate that there is a difference between the commercial financial statements and fiscal, namely differences in the basis of taxpayer recognition, negative tax adjustments including negative correction costs, namely CSR costs and depreciation costs. The implication of this research is that corporate entities need to carry out fiscal reconciliation, because there are differences in cost recognition between fiscal regulations and accounting standards that apply in Indonesia.